COMPARISON OF THE EXPERIMENTAL PERFORMANCE OF A THERMOSYPHON WITH ITS THERMAL DESIGN - Machado, P. L. O.; Souza, R. O.; Machado, V. O. O.; Santos, P. H. D.; Szmoski, R. M.; Antonini Alves, T. (Revista de Engenharia Térmica, 2022)
A thermosyphon is a gravity-assisted heat pipe used to improve heat transfer in several applications. Its main feature is the use of latent heat of vaporization to transmit heat at high rates over considerable distances with a small decrease in temperature. In this work, the experimental performance of a thermosyphon was compared with its thermal design, in order to verify its correct operating. The thermosyphon was manufactured from a copper tube with an outer diameter of 22.23mm, an inner diameter of 20.80mm, and a total length of 840mm. The working fluid used was distilled water with a filling ratio of 50% of the evaporator volume. The evaporator has a length of 650mm, while the adiabatic section and condenser have lengths of 80mm and 110mm, respectively. The condenser was cooled by water forced convection and the evaporator was heated by Joule’s effect. Experimental tests were performed for a heat load of 80 to 140W in a position at 25º from the horizontal (evaporator above the condenser). The thermal analysis of the thermosyphon was performed from thermocouples arranged in their regions, as well as the value of the thermal load dissipated by it. Some specific points of the experimental apparatus were identified for possible adjustments, such as better insulation, different manifold, and different water flow conditions. The thermosyphon operated as expected in all the analyzed aspects – temperature distribution, thermal resistance, thermal design’s heat load, and thermal and exergy efficiencies – which showed that the methodology used to its construction is adequate.